Analysis of Factors Affecting Brand Trust Toddler Care Products in Jabodetabek Brand Study: Zwitsal Baby - Claresta Purnama; Rudy Handoko; Alavi Ali (Jurnal Ilmu Manajemen & Ekonomika, 2020)
Parents, especially mother whose role as decision maker in purchasing baby toiletries, certainly want to provide the best products for their baby. Baby toiletries that known as high functional risk products, make mothers really have to be aware and very careful when making decisions. In that highrisk situation, moth-ers can minimize the risk by choosing a brand that they trust. Through this quantitative research by distrib-uting questionnaires to mother who use Zwitsal Baby products in Jabodetabek, obtained the results of measurements of the factors forming the brand trust. This study aims to measure how strong rhe influence of the factors forming the brand trust, the influence of the mediator variables, and moderator variabels de-rived from mothers’ personality traits. The results of this study indicate that the forming aspects of brand trust, which are brand predictability, brand innovativeness, and brand intimacy have a positive and signifi-cant impact on cognitive and affective brand trust. Cognitive brand trust which is a mediator variable in this study, also have a positive and significant influence in the formation of affective brand trust. As for the moderator vaiable, the study shows that openness does not influence the formation of brand trust, but con-scientiousness and agreeableness have a significant relationship, but has a fairly weak influence. The result of this research can be used to develop or form brand trust in baby toiletries products, especially for Zwitsal Baby brand.